EMCDDA-Europol 2017: annual report on the implementation of Council Decision 2005/387/JHA (Implementation reports, 2018)
This report presents the key activities performed by the EMCDDA and Europol in 2017, with details on all the relevant activities in support of the implementation of Council Decision 2005/387/JHA on the information exchange, risk assessment and control of new psychoactive substances, including new psychoactive substances notified in 2017, Joint Reports produced, risk assessments conducted and public health alerts and advisories issued.